$Since,wehavebeengiventhefunctionG\left(x\right)=2x-\frac{1}{3}\phantom{\rule{0ex}{0ex}}OurAimistofindthefollowingfuntionvalues:-\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}\left(a\right)G\left(\frac{-13}{4}\right)\phantom{\rule{0ex}{0ex}}Solution\Rightarrow G\left(\frac{-13}{4}\right)=2\left(\frac{-13}{4}\right)-\frac{1}{3}=\frac{-41}{6}$
$\left(b\right)G\left(0.5\right)\phantom{\rule{0ex}{0ex}}Solution\Rightarrow G\left(0.5\right)=2(0.5)-\frac{1}{3}=1-\frac{1}{3}=\frac{2}{3}\phantom{\rule{0ex}{0ex}}\left(c\right)G(-7)\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}Solution\Rightarrow G(-7)=2(-7)-\frac{1}{3}=-14-\frac{1}{3}=\frac{-43}{3}$